NALISIS PENDAPATAN USAHA KURSI ROTAN PADA UKM MEUBEL SUMBER ROTAN TOHITI DI KOTA PALU - Marhawati Mapatoba, Kahar, (AGROTEKBIS, 2016)
Research goal is to know the income obtained by enterprise of chairs rattan on small medium enterprise of Sumber Rotan Tohiti Meubel at Palu City. The research conducted at Tanjung Manimbaya street. Analysis used was the income analysis of rattan chairs firm on small medium enterprise of Sumber Rotan Tohiti Meubel at Palu City, consists of 3 types of item of furniture that are Margin chairs desk, rilex chairs desk and sofa chairs desk. The results research showed that the total product income of 3 type of the furniture was Rp. 13.096.899.Â